Digital Forensic Analysis of WhatsApp Business Applications on Android-Based Smartphones Using NIST - William Barkem; Jeckson Sidabutar (Universitas Bumigora, 2023)
WhatsApp Business is an Android application that can be downloaded on Playstore to serve small business owners. This provides an opportunity for criminals to take advantage of the app’s features. These crimes can take the form of fraud, misdirection, and misuse of applications, so digital forensics is necessary because there has never been any research that has done this. This study aims to obtain digital evidence and is carried out on Android smartphones with the WhatsApp Business application installed with four scenarios tested. This study uses the NIST SP 800-101 Rev 1 guidelines with four stages: preservation, acquisition, inspection & analysis, and reporting. The forensic method used is static forensics using the MOBILedit forensic express forensic tools and SysTools SQLite Viewer. The results of this study in scenario 1, by not deleting, get a 100% percentage. Then, scenario 2, namely direct write-off, gets a percentage of 71%. Furthermore, scenario 3, namely uninstalling the application, does not get digital evidence, and scenario 4, namely deleting data through the application manager, also does not get any evidence. The contribution of this research is expected to be a reference in uncovering cases in the WhatsApp Business application with digital forensics.